The genus Boreomysis G.O. Sars, 1869 (Peracarida, Mysida, Mysidae) in western Mexico - Hernández-Payán, J.c.; Hendrickx, M.e. (Zootaxa, 2024)
Two species of the genus Boreomysis, B. arctica (Krøyer, 1861) and B. californica Ortmann, 1894, were collected in western Mexico. In the eastern Pacific, Boreomysis arctica had previously been recorded from the Bering Sea to southern California. New records in Mexico extend its southernmost distribution limit to 17°25’33” N, off SW Mexico, including samples collected off the west coast of the Baja California Peninsula and the Gulf of California (25 specimens in 12 samples). In the eastern Pacific, B. californica has been reported from Alaska to Peru, with its type locality in the Central Gulf of California. During this study, it was by far the most frequently species collected (343 specimens in 58 samples) off the west coast of the Baja California Peninsula in the Gulf of California, and off SW Mexico (south to 16°58’00” N).